Needle‐free injection system delivery of ZyCoV‐D DNA vaccine demonstrated improved immunogenicity and protective efficacy in rhesus macaques against SARS‐CoV‐2. Issue 2 (18th January 2023) - Yadav, Pragya D.; Kumar, Sanjay; Agarwal, Kshitij; Jain, Mukul; Patil, Dilip R.; Maithal, Kapil; Mathapati, Basavaraj; Giri, Suresh; Mohandas, Sreelekshmy; Shete, Anita; Sapkal, Gajanan; Patil, Deepak Y.; et al.
Abstract: The apprehension of needles related to injection site pain, risk of transmitting bloodborne pathogens, and effective mass immunization have led to the development of a needle‐free injection system (NFIS). Here, we evaluated the efficacy of the NFIS and needle injection system (NIS) for the delivery and immunogenicity of DNA vaccine candidate ZyCoV‐D in rhesus macaques against SARS‐CoV‐2 infection. Briefly, 20 rhesus macaques were divided into 5 groups (4 animals each), that is, I (1 mg dose by NIS), II (2 mg dose by NIS), III (1 mg dose by NFIS), IV (2 mg dose by NFIS) and V (phosphate‐buffer saline [PBS]). The macaques were immunized with the vaccine candidates/PBS intradermally on Days 0, 28, and 56. Subsequently, the animals were challenged with live SARS‐CoV‐2 after 15 weeks of the first immunization. Blood, nasal swab, throat swab, and bronchoalveolar lavage fluid specimens were collected on 0, 1, 3, 5, and 7 days post infection from each animal to determine immune response and viral clearance. Among all the five groups, 2 mg dose by NFIS elicited significant titers of IgG and neutralizing antibody after immunization with enhancement in their titers postvirus challenge. Besides this, it also induced increased lymphocyte proliferation and cytokine response. The minimal viral load post‐SARS‐CoV‐2 challenge and significant immune response in the immunized animals demonstrated the efficiency of NFIS in delivering 2 mg ZyCoV‐D vaccine candidate.